Achieving abiotic stress tolerance in plants through antioxidative defense mechanisms - Mishra, Neelam; Jiang, Chenkai; Chen, Lin; Paul, Abhirup; Chatterjee, Archita; Shen, Guoxin (Frontiers in plant science, 2023)
Climate change has increased the overall impact of abiotic stress conditions such as drought, salinity, and extreme temperatures on plants. Abiotic stress adversely affects the growth, development, crop yield, and productivity of plants. When plants are subjected to various environmental stress conditions, the balance between the production of reactive oxygen species and its detoxification through antioxidant mechanisms is disturbed. The extent of disturbance depends on the severity, intensity, and duration of abiotic stress. The equilibrium between the production and elimination of reactive oxygen species is maintained due to both enzymatic and non-enzymatic antioxidative defense mechanisms. Non-enzymatic antioxidants include both lipid-soluble (α-tocopherol and β-carotene) and water-soluble (glutathione, ascorbate, etc.) antioxidants. Ascorbate peroxidase (APX), superoxide dismutase (SOD), catalase (CAT), and glutathione reductase (GR) are major enzymatic antioxidants that are essential for ROS homeostasis. In this review, we intend to discuss various antioxidative defense approaches used to improve abiotic stress tolerance in plants and the mechanism of action of the genes or enzymes involved.